Etiology and Control of Citrus Canker Disease in Kavre - Dhakal, Dinesh; Regmi, Chiranjivi; Basnyat, Sital Raj (Nepal Journal of Science and Technology, 2010)
Citrus canker, caused by the bacterium Xanthomonas citri (Hasse) occurs in large areas of the world's citrus growing countries including Nepal. Though the disease has serious effect in Nepal, this is the first detailed study carried out to isolate the pathogen and confirm it by available biochemical tests and pathogenicity test. Furthermore, the study was intended to find the proper and economical control measure to combat disease in citrus orchards. The causative agent of the disease was isolated from the diseased plants and pure culture was obtained. The isolated pure culture was subjected to Gram staining, catalase test, oxidase test, O-F test, starch hydrolysis, nitrate reduction test, methylred test, Voges-prausker test, indole production test, urease test and carbohydrate utilization test. To re-confirm it, pathogenicity test was conducted on host plant and after the appearance of the typical citrus canker lesion on host, the bacteria was re-isolated, thus proving the Koch's postulates. Different controlling chemicals, copperoxychloride (2.5%), copperoxychloride + kasugamycin (1000X), bordeaux mixture 1% and 2% were sprayed to the plants in citrus orchard at Dhulikhel and the decrease in disease severity after spraying of the chemicals was calculated with reference to the plants that were not sprayed with the chemicals. It was observed that spraying of the chemicals help in decreasing the disease severity. The chemical spray however was not able to eradicate the disease. The study concluded that Xanthomonas citri was the causative agent of the disease citrus canker and copper based chemicals when sprayed very early with the appearance of first symptoms of the disease could eliminate it in citrus fruits to minimum level. Key words: Copper fungicides; Citrus canker; Lime; Xanthomonas citri; Acid lime; Citrus aurantifolia DOI: 10.3126/njst.v10i0.2824 Nepal Journal of Science and Technology Volume 10, 2009 December Page: 57-61